Dzikir Psychotherapy as Therapy in Counseling for Depression: Literature Review - Rahmi, Harsa Afifatur; Lestari, Yuliana Intan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to explore the effectiveness of dhikr psychotherapy in reducing depressionamongcollege students. The research methodemployedisa literature review, involving the collection ofrelevant literature and research findings related to dhikr therapy, Islamic psychotherapy, and depression. This study includes 10 articles published between 2014 and 2024, whichdemonstratethat dhikr psychotherapy has a significant impact onloweringdepression levels. The results indicate that dhikr therapy,particularlyistighfar dhikr, cansubstantiallyreduce depressionsymptoms.Dhikrservesas a form of worship that provides emotional and spiritual calm,while also enhancingmental and physical well-being. This therapy not onlyalleviatessymptoms of depression but also strengthens an individual's spiritual and emotionalresilience.